An Empirical Study of Extended Marketing Mix for PPE Manufacturing Companies - Digvijay Singh, Arti Chandani, Ankita Bhatia (International Journal of Modern Agriculture, 2020)
The Personal Protective Equipment has become an indispensable part of life in the present time and demand keeps on growing day by day. Manufacturing Personal protective equipment such as masks, gloves, coveralls, face shield, goggles etc. has become a new norm as many hospitals, research Labs and Pathology labs require it on a daily basis. It is not only restricted to hospital staff, but front-line staff and even the normal people also require it daily. The aim of this research is to test whether different types of companies use the same marketing mix strategies which want to manufacture Personal Protective Equipment (PPE). This research paper will help us to identify whether a Government, privately owned or Foreign-based companies are using the same kind of marketing mix strategy i.e., Product, Price, Place, Promotion, People, Process and Physical evidence. This research paper is based on quantitative analysis methods. The respondents are the manufacturers from the Personal Protective Equipment from different parts of the world. The survey questionnaire is made on google forms and is floated to many different organizations across India and other countries who are currently producing Personal Protective Equipment (PPE). Researchers have used Reliability test, ANOVA and sample t-tests to analyse the data and test hypothesis using SPSS 25 version in order to retrieve the results. The result shows that there is no significant difference between 7 P’s of Marketing mix and the types of companies whether government, Private and foreign sector.